2005
DOI: 10.1038/ncb1241
|View full text |Cite
|
Sign up to set email alerts
|

CSN facilitates Cullin–RING ubiquitin ligase function by counteracting autocatalytic adapter instability

Abstract: The COP9 signalosome (CSN) is known to bind cullin-RING ubiquitin ligases (CRLs) and to promote their activity in vivo. The mechanism of this stimulation has remained enigmatic because CSN's intrinsic and associated enzymatic activities paradoxically inhibit CRL activity in vitro. Reconciling this paradox, we show here that Csn5-catalysed cullin (Cul) deneddylation and Ubp12-mediated deubiquitination cooperate in maintaining the stability of labile substrate adapters, thus facilitating CRL function. Various fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
171
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 27 publications
8
171
0
1
Order By: Relevance
“…In addition, the CSN is associated with a deubiquitinating enzyme called USP15 and with kinases such as CK2 and PKD [30,31,39].…”
Section: Caspase Cleavage Of Csn6 Is Accompanied By Cleavage Of Rbx1mentioning
confidence: 99%
“…In addition, the CSN is associated with a deubiquitinating enzyme called USP15 and with kinases such as CK2 and PKD [30,31,39].…”
Section: Caspase Cleavage Of Csn6 Is Accompanied By Cleavage Of Rbx1mentioning
confidence: 99%
“…Multiple studies from a range of organisms have shown that CSN interacts with Cullin-RING E3s and that proper E3 function is dependent on CSN and more specifically on CSN5-mediated deneddylation Schwechheimer et al, 2001;Schwechheimer, 2004). Some recent studies suggest that deneddylation is required for E3 subunit stability or E3 complex assembly (Hetfeld et al, 2005;Wee et al, 2005;Wu et al, 2005;Bornstein et al, 2006). Furthermore, it has been proposed that CSN is part of a proteasome-related complex (Peng et al, 2001(Peng et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Even though deneddylation inactivates CRLs in vitro [18][19][20] , the CSN promotes ubiquitin ligase activity in vivo in various organisms 17,21,22 . This paradoxical behaviour can at least partially be explained by the fact that in cells constitutively neddylated complexes ubiquitylate their own subunits, leading to autodegradation 23 .…”
mentioning
confidence: 99%